Mukhadarah Practices Among Farmers: A Study Of Islamic Economics In Supporting Sustainable Agricultural Development Policies - Syahidah Rahmah (JURNAP: Jurnal Administrasi Publik, 2025)
Agricultural transactions conducted before harvest remain a common practice among rural communities as a strategy to address financial needs and maintain farming activities. This study aims to analyze mukhadarah practices among mango farmers in Marayoka Village, Jeneponto Regency, from the perspective of Islamic economics and examine their relevance to sustainable agricultural development policies. This study employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and documentation involving farmers, buyers, religious leaders, and village officials. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings indicate that mukhadarah transactions are conducted through the sale of mango fruits before harvest based on estimated production and mutually agreed prices. The practice provides economic benefits by enabling farmers to obtain quick access to capital and reducing marketing risks. From the perspective of Islamic economics, mukhadarah fulfills the principles of mutual consent (an-taradhin) and contractual agreement, although it still contains potential elements of gharar due to uncertainty regarding the quantity and quality of future harvests. Furthermore, the practice contributes to sustainable agricultural development by supporting the continuity of farming activities and improving farmers' access to financial resources. Therefore, strengthening the principles of justice, transparency, and risk-sharing mechanisms is essential to ensure that mukhadarah practices provide greater welfare for farmers while supporting sustainable agricultural development